The effect of nature on creativity through mental imagery - Aaron C. Drake; Fiza Hasan; Arianna Gibson; Julia W. Y. Kam (PLoS ONE, 2025)
Immersion in nature has been linked to wide-ranging benefits on mental health and cognitive functions, from reducing stress to enhancing creativity. However, a walk in nature is not always feasible, and whether a proxy for nature immersion via a mental walk in nature can elicit the same benefits as a physical walk remains largely unknown. Accordingly, the current study utilized guided imagery to examine whether a mental walk in nature would improve creativity in general and when compared to a mental walk in an urban environment. We implemented a within-subjects design, wherein participants completed both mental walk conditions (in a nature and urban environment) at least five days apart in counterbalanced order on an online platform. During each session, participants (N = 97) completed two pre-walk tasks assessing convergent (measured by the Remote Associates Test) and divergent creative thinking (measured by the Alternate Uses Test), followed by a mental walk in either a nature or urban environment, then finally the identical two post-walk creativity tasks. After five days, they repeated the same procedure with a mental walk in the other environment. While comparisons of post-walk creativity scores between the nature and urban environment did not significantly differ from each other, the comparisons between the pre- and post-walk creativity scores revealed a significant improvement in convergent creative thinking in the nature environment condition, but not the urban environment condition. Our results suggest that taking a mental walk in nature can enhance at least one aspect of creativity, therefore providing preliminary evidence for the potential to access the creative benefits of mentally immersing ourselves in nature. These findings have important implications for those who wish to enjoy the benefits of nature but are unable to readily access nature physically.